A Strong Brand as a Determinant of Purchase the Case of Sectors, where Advertising in Mass Media Is Banned – on the Example of the Polish Spirits Sector - Katarzyna Liczmanska; Agnieszka M Wisniewska (Managerial Economics)
The purpose of the paper is the assessment of the significance of a strong brand in the process of competing for clients as well as in the client`s decision making processes in a situation where advertising in mass media is almost completely banned. The paper presents results of two complementary studies. The first study was carried out by means of personal interviews on a trial group of 1501 individual respondents in 2007 in Poland. The second study was carried out using personal or Internet questionnaires on a trial group of 16 companies producing or importing spirits. The collected material showed that clients pointed to a strong brand as the key factor influencing their choice of top market alcohols. All representatives of producers see the need for building strong brands and declare having such brands in their offer. Building strong product brands is possible even in sectors in which mass media advertising is prohibited or for some reason cannot be used. The conceptual model proposed by the authors suggests what should be taken into account when creating a strong brand in sectors where adverting may not be used for this purpose.